A Clinico- Pathological Study On Eosinophilic Patients And Its Management With Haridra Khanda And Shirishadi Yoga - Singh, Sunil Kumar; Panda, Pradip Kumar; Nayak, Utkalini; Mishra, P K (International Research Journal of Ayurveda & Yoga, 2020)
Introduction- Eosinophilia is a pathological condition often manifest cough, dyspnoea, allergic reaction, parasite infection and eczema etc. in human body. No such direct co-related disease is mentioned in Ayurvedic classes but may be aggravated due to vata-kapha predominant condition of the body. Material and methods – 30 patents of Group A- (15 patients) and Group B- (15 patients) were registered from OPD and IPD of Govt. Ayurvedic College & Hospital, Balangir, presented with cough, sputum, dyspnea, aggravation after exposure to cold climate, itching, red rashes, dry – cracked skin etc. Which are similar with the diseases Bronchial Asthma and Dermatitis. Blood sample show increased eosinophilia condition in DC, AEC, and were diagnosed as case of Eosinophilic patients. After diagnosis they were trial with Ayurvedic formulations of Haridra khanda in Group A- and Shirishadi yoga in Group B, given 5grms each thrice a day for a period of 30 days with water respectively. The subjective and objective parameters of assessment were evaluated in 15th and 30th day from the day of initiation of trial up to 30 days in order to find the efficacy of both the trials by statistical paired ‘t’ test. Observation and results:- It has been observed that the trial drug Group-A patients is highly significant to reduce Eosinophil, A.E.C and ESR after 30 days of treatment with p-value <0.001. Discussion and Conclusion- Eosinophilia is a Tridoshaja vyadhi with the main involvement dosha- Kapha and Vata. Eosinophilia is mostly due to hypersensitivity reactions induced by different allergens.. Both the drugs had improved by reducing the levels of eosinophil, AEC and ESR in patients but Haridra khanda inferred better result as compare to Shirishadi yoga. No side effect was noticed during clinical study Haridra khanda, Shirishadi yoga.